Kontrol Diri dengan Perilaku Konsumtif Pada Ibu Rumah Tangga - Andi Nur Anisah Atmaja; Nani Restati Siregar; Eva Herik (Jurnal Sublimapsi, 2023)
Consumptive behavior is a human tendency to use unlimited consumption and is more concerned with wants than needs. If a person's self-control is at a high level, then a person is able to control himself not to buy an item. This study aims to determine the relationship between self-control and consumptive behavior in housewives. The subjects of this study were 100 people, from a total population of 5,124 housewives in the Kambu District. The sampling technique in this study used a cluster random sampling technique. The data collection method uses a self-control scale with consumptive behavior. The data analysis technique uses Pearson's Product Moment correlation method. The results of the data analysis showed that the correlation coefficient was -0.422 and the correlation significance (p) was 0.000. So it can be concluded that there is a significant negative relationship between self-control and consumptive behavior in housewives.